Self-Regulated Learning Strategies and Their Effects on Math Performance of Pre-University International Students in Malaysia - Tang Eng Loong (Journal of Education and Vocational Research, 2012)
The study examined any differences in self-regulated learning (SRL) strategies between two groups of international students in the Monash University Foundation Year (MUFY) program in Malaysia, in which one group of 58 international students in their first semester, and another group of 18 international students in their second and third semesters. It followed by examining the effect of the use of SRL strategies on math performance for both groups. The Learning and Study Strategies Inventory (LASSI) was used to measure the use of SRL strategies among international students, and the final score of the most manageable mathematical subject was used to measure their math performance. The result indicated that first-semester international students used as many SRL strategies as second- and thirdsemester international students, and no significant difference in math performance between the groups was found. The result also revealed that attitude towards academic tasks; motivation level and test taking strategies were positively associated with math performance of first-semester international students, while anxiety towards tests, attitude towards academic tasks and test taking strategies were positively associated with second- and third-semester international students’ math performance. Moreover, math performance of first-semester international students was significantly predicted by attitude towards academic tasks and test taking strategies, but second- and third-semester international students’ math performance was not significantly predicted by any SRL strategies.